Heuristics for the assessment of interfaces of mobile devices - Machado Neto, Olibário; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Although usability heuristics are a useful tool for the evaluation of interactive user interfaces, the traditional Nielsen's heuristics were created without mobile computing in mind. Other heuristics proposed for mobile applications, usually derived solely from the traditional heuristics, consider aspects that are not directly related to the software's visualization layer to which user interfaces belong. In this study, we extended Nielsen's heuristics to derive other heuristics specifically for the usability evaluation of mobile user interfaces. Two separate sets of specialists evaluated an Android application using Nielsen's heuristics and the heuristics we derived: the latter allowed the identification of more usability problems.